2016
DOI: 10.4236/jtst.2016.23007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spinning Parameters on Thick, Thin Places and Neps of Rotor Spun Yarn

Abstract: Defect free yarn is a great demand for spinner, knitter, and weaver and also other textile personnel because numerous end products from knit apparels to woven fabrics, from towels to sheets and from carpets to industrial fabrics characteristics significantly depend on the physical properties of yarn. The qualities of rotor yarn are really directed by spinning parameters. The aim of this study is to observe the effect of spinning parameters such as rotor diameter and speed on thick, thin places and neps of yarn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…It is also known that Thick + 50 values are highly correlated to rotor speed, rotor diameter, yarn count and spinning. 30,41 Rotor diameter is not included in this study since it was not supplied in the dataset procured from the textile plant. Yarn count and spinning are both found to be significant by ANOVA.…”
Section: Resultsmentioning
confidence: 99%
“…It is also known that Thick + 50 values are highly correlated to rotor speed, rotor diameter, yarn count and spinning. 30,41 Rotor diameter is not included in this study since it was not supplied in the dataset procured from the textile plant. Yarn count and spinning are both found to be significant by ANOVA.…”
Section: Resultsmentioning
confidence: 99%
“…The absorption peaks at 2891, 1368, 1314, 1160, and 1024 cm 21 also belong to the functional groups (CH, CH 2 , CH 3 , C-O-C) in the structure of cellulose. The absorption peaks in the range of 800-897 cm 21 show the symmetrical stretch vibrations of the Si-CH 3 and Si-O-Si groups in PDMS. According to the results of FTIR analyses, Si-CH 3 and Si-O-Si bonds were detected.…”
Section: Evaluation Of Ftir Analysismentioning
confidence: 99%
“…There are many scientific studies on the recycling of textile wastes. A large part of these studies are on the determination of the physical properties of recycled yarn 14,[16][17][18][19][20][21][22][23] and fabrics produced from recycled yarn. 11,[24][25][26][27][28][29][30][31] However, in the literature, it is seen that the studies on functional and high value-added fabrics obtained from recycled yarns are quite limited.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have already studied the effect of waste on yarn quality from different perspectives. The results of several investigations have revealed that the waste of different sections of the apparel industry significantly affects the physical and mechanical properties of the yarn [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Jamshaid et al.…”
Section: Introductionmentioning
confidence: 99%